The persistence of indigenous mystical cosmology among Bemba Catholics in Mpika, Zambia - Armstrong Chanda (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2026)
In the contemporary Mpika District of Zambia, Bemba Catholics have continued to maintain their belief in and practice of the mystical powers of the indigenous Bemba cosmology and spirituality. This is despite a century of evangelisation and condemnation of the mystical beliefs and practices. To understand the enduring nature of this belief and the reasons for its endurance, a descriptive case study was employed within a qualitative research approach. In-depth interviews and focus group discussions were used to collect data, and thematic framework analysis was utilised to analyse the data. Lay Bemba Catholics, Catholic clergy, and community headmen were studied. A homogeneous purposive sampling method was applied to select 34 participants. Bemba Catholics integrate traditional beliefs and practices into their Catholic lives, shaped by their native cosmological worldview. This merging of cultural values influences their religious practices and identity, highlighting the intersection of socio-religious and cultural factors behind the persistence of this belief. The pervasive fear and anxiety associated with mystical reality also contribute to their belief in supernatural powers. The study contributes to the appreciation of the relevance of indigenous belief and practice in modern Christians’ experience and to awareness of cultural sensitivity in dialogue with indigenous African belief and practice. The study recommends that the Church engage with knowledgeable indigenous people in African beliefs and practices to appreciate and enhance the coexistence of indigenous beliefs in supernatural powers and the Catholic faith.